Equity valuation and portfolio management - Fabozzi, Frank J.; Markowitz, H. (Harry), 1927- (Hoboken, N. J. : John Wiley & Sons, 2011)
'A detailed look at equity valuation and portfolio management Equity valuation is a method of valuing stock prices using fundamental analysis to determine the worth of the business and discover investment opportunities. In Equity Valuation and Portfolio Management Frank J. Fabozzi and Harry M. Markowitz explain the process of equity valuation, provide the necessary mathematical background, and discuss classic and new portfolio strategies for investment managers. Divided into two comprehensive parts, this reliable resource focuses on valuation and portfolio strategies related to equities.* Discusses both fundamental and new techniques for valuation and strategies* Fabozzi and Markowitz are experts in the fields of investment management and economics* Includes end of chapter bullet point summaries, key chapter take-aways, and study questions Filled with in-depth insights and practical advice, Equity Valuation and Portfolio Management will put you in a better position to excel at this challenging endeavor'--Back cover.
ch. 18. Equity Portfolio Selection in Practice / Dessislava A. Pachamanova and Frank J. Fabozzi -- ch. 19. Portfolio Construction and Extreme Risk / Jennifer Bender, Jyh-Huei Lee, and Dan Stefek -- ch. 20. Working with High-Frequency Data / Irene Aldridge -- ch. 21. Statistical Arbitrage / Brian J. Jacobsen.
Includes bibliographical references and index.
Keywords: Corporations -- Valuation; Portfolio management